Sectarian Conflict in Egypt : Coptic Media, Identity and Representation. - Iskander, Elizabeth (Routledge studies in Middle Eastern politics., 2012)
In light of the Egyptian uprising in early 2011, understanding the dynamics that are shaping Egyptian politics and society is more crucial than ever as Egypt seeks to re-define itself after the Mubarak era. One of the most controversial debates concerns the place of religion in Egypt's political future. This book examines the escalation in religious violence in Egypt since 2005 and the public discourses behind it, revealing some of the complex negotiations that lie behind contestations of citizenship, Muslim-Christian relations and national unity. Focusing on Egypt's largest religiou.